Governing for a sustainable food system planning - Marat-Mendes, T.; Borges, J.; Mélice, A.; Lopes, R. (International Conference Fifty Years of Local Governance 1980-2030, 2018)
Food security, sustainable urban agriculture and improved nutrition constitute three specific goals identified by the Milan Agreement, the UN 2030 Agenda and the New Urban Agenda to assure sustainable urban transitions, which should concern local governance. However, evidence suggests that the food system has not been fully integrated within local policies. This presentation introduces some preliminary contributions of an on-going research project (SPLACH – Spatial Planning for Change), which aims to identify urban planning policies capable of sustainable transitions towards low-carbon cities. Thus, a first evaluation of the integration of the food system within local planning policies, specifically in Lisbon Metropolitan Area (AML) is here discussed, seeking to disclose the evolution of main strategies in the municipal planning instrument (PDM) of the AML municipalities.